Hard landscape trend analysis: a case study at Perak Tengah district / Ahmad Zamil Zakaria, Mohd Sabrizaa Abd Rashid and Syazwani Ahmad - Zakaria, Ahmad Zamil; Abd Rashid, Mohd Sabrizaa; Ahmad, Syazwani (UiTM Press, 2016)
Hard landscape as known is made up of man made materials found in gardens or in house compounds. At the moment it is difficult to obtain accurate information on the existence of hard landscape in the compound of Malay community houses. This is due to the hard landscape of the Malay community which is not very significant (intangible factors) compared to soft landscape elements which are more prominent (tangible factors). The aim of this study was to identify the needs and functions of each hard landscape elements in the Perak Malay landscape. The objective of this study was to determine the elements of traditional hard landscape and its use in the present. As a conceptual framework, this study will focus on the results of previous research findings that are relevant to the "user preference" of hard landscape elements used by the Malay community. Quantitative and qualitative methods were used to obtain information for this study. Case studies include the Malay traditional house in the Perak Tengah District. Researchers expect the study to be a benchmark for the survey in other districts in Perak. The results of this study concluded that the hard landscape element that is used by the Malay community is not the same as used by other communities in the world. Differences have made the study more interesting, and this information can be used by other researchers in the future.